Using correlation matrices in predicting airline performance - O. G. Feoktistova; D. Yu. Potapova (Омский научный вестник)
The article considers the issue of making forecasts of the main indicators of the activities of airlines for their effective functioning in the air transportation market. It describes the life cycle of airlines and provides a classification of the forecasts that are currently being made. The interrelation of correlations of the key parameters of the airline’s functioning is considered, the use of correlations in forecasting is shown, actual calculations are presented, and a significant increase in forecast accuracy when using this forecasting method is demonstrated.